2011
DOI: 10.1136/bmj.d2392
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the NICE guideline recommending cessation of antibiotic prophylaxis for prevention of infective endocarditis: before and after study

Abstract: Objective To quantify the change in prescribing of antibiotic prophylaxis before invasive dental procedures for patients at risk of infective endocarditis, and any concurrent change in the incidence of infective endocarditis, following introduction of a clinical guideline from the National Institute for Health and Clinical Excellence (NICE) in March 2008 recommending the cessation of antibiotic prophylaxis in the United Kingdom.Design Before and after study.Setting England.Population All patients admitted to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
2
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(162 citation statements)
references
References 26 publications
5
140
2
15
Order By: Relevance
“…After the National Institute for Health and Care Excellence recommended that the use of antibiotic prophylaxis for high-risk cardiac patients be discontinued in the United Kingdom, an initial 78.6% reduction was seen in their prescription. Before this revision, general dental practitioners wrote 91.9% of all antibiotic prophylaxis prescriptions in the United Kingdom (Thornhill et al, 2011).It would be useful to gather data on the practices of clinicians before the updated recommendations to determine whether a decline is evident with the American Dental Association and the American Academy of Orthopaedic Surgeons recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…After the National Institute for Health and Care Excellence recommended that the use of antibiotic prophylaxis for high-risk cardiac patients be discontinued in the United Kingdom, an initial 78.6% reduction was seen in their prescription. Before this revision, general dental practitioners wrote 91.9% of all antibiotic prophylaxis prescriptions in the United Kingdom (Thornhill et al, 2011).It would be useful to gather data on the practices of clinicians before the updated recommendations to determine whether a decline is evident with the American Dental Association and the American Academy of Orthopaedic Surgeons recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have showed that there is no obvious increase in the incidence of infective endocarditis cases or deaths in the two years after the guideline was introduced about the cessation prescribing antibiotic prophylaxis. The findings support the cessation of prescribing antibiotic prophylaxis [60]. Therefore further clinical trials should determine if periodontal intervention combined with drug therapy would reduce the incidence of CVD.…”
Section: Maharajmentioning
confidence: 75%
“…Cunha et al documented a similar case which, resulted in a cerebral vascular accident, embolic occlusion of the leg, and mitral valve replacement [37] . On the other hand, a reduction of 78.6% in prescribing antibiotics was noticed after the unveiling of NICE guideline [38] . The French agency for Health Product Health Safety advices against or contraindicates dental facial surgery, bone surgery, periodontal surgery, root canal treatment in these patients except under emergency situations, as these patients are prone to high risk of infection [39] .…”
Section: Antibiotic Prophylaxis To Prevent Infective Endocarditismentioning
confidence: 99%
“…Patients treated with corticosteroids for a long time may require an additional need of corticosteroids to prevent adrenal crisis. The dose is doubled if the patient is on [30][31][32][33][34][35][36][37][38][39][40] mg per day of hydrocortisone for a month. An additional supplement is not required if the dose is up to 30 mg per day of hydrocortisone.…”
Section: Antibiotic Regimen With Precautionmentioning
confidence: 99%